2000
DOI: 10.1046/j.1365-2044.2000.01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia during upper gastrointestinal endoscopy with and without sedation and the effect of pre‐oxygenation on oxygen saturation

Abstract: SummaryIn Study A, the incidence of arterial oxygen desaturation was studied using pulse oximetry (S a o 2 ) in 100 sedated and 100 nonsedated patients breathing room air who underwent diagnostic upper gastrointestinal endoscopy. Hypoxia (S a o 2 92% or less of at least 15 s duration) occurred in 17% and 6% of sedated patients and nonsedated patients, respectively (p , 0.03). Mild desaturation (S a o 2 94% or less and less than 15 s duration) occurred in 47% of sedated patients compared with 12% of nonsedated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 16 publications
2
42
0
7
Order By: Relevance
“…Furthermore, the occurrence of bradycardia and hypotension ranges between 6 and 19% in various studies [27,28]. In addition, upper GI endoscopy seems to be a risk factor for hypoxemia with or without pharmacologic sedation [29]. Severe desaturation (SaO 2 <90%) was found in up to 6% of patients with upper GI endoscopy without sedation, at least in one study [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the occurrence of bradycardia and hypotension ranges between 6 and 19% in various studies [27,28]. In addition, upper GI endoscopy seems to be a risk factor for hypoxemia with or without pharmacologic sedation [29]. Severe desaturation (SaO 2 <90%) was found in up to 6% of patients with upper GI endoscopy without sedation, at least in one study [30].…”
Section: Discussionmentioning
confidence: 99%
“…4 One study that defined hypoxia as arterial oxygen desaturation less than 92% for at least 15 seconds found that hypoxia developed in 17% of sedated patients who underwent upper GI endoscopy when breathing room air. 11 Transient hypoxia developed even in patients who receive routine supplemental oxygen in 16% of routine endoscopic procedures with sedation. 12 The proportion of patients in our study in whom transient hypoxia developed, requiring an increase in oxygen, was slightly lower but consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Sedation might primarily cause hypoxia by inducing respiratory depression, while the presence of an endoscope may also cause hypoxia by narrowing the upper airway (19). In a study conducted on 330 patients, Banks et al (20) demonstrated that the arterial oxygen pressure was considerably decreased in patients with sedation compared to those without, while Wang et al (19) observed hypoxia in both patients with and without sedation, but stressed that sedation significantly increased hypoxia. Yazawa et al (18) found a reduction in arterial oxygen pressure in the group with sedation compared to that without, but the reduction was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%